Drivers of Financial Integration : Implications for Asia - Ananchotikul, Nasha (IMF Working Papers; Working Paper ;, 2015)
Deeper intraregional financial integration is prominent on Asian policymakers' agenda. This paper takes stock of Asia's progress toward that objective, analyzing recent trends in cross-border portfolio investment and bank claims. Then, it investigates the drivers of financial integration by estimating a gravity model of bilateral financial asset holdings on a large sample of source and destination countries worldwide, focusing in particular on the role of regulation and institutions. The paper concludes that financial integration in Asia could be enhanced through policies that lower informational frictions, continue to buttress trade integration and capital market development, remove restrictions to foreign flows and bank penetration, and promote a common regulatory framework.